Analisis Penerapan Cost Recovery Method Dan Percentage Of Completion Method Berdasarkan PSAK 34 Terhadap Laba Kotor Perusahaan PT Mitra Menara Mandiri - Andres, Jhonatan; Pardede, Robert Pius (Institut Bisnis dan Informatika Kesatuan, 2018)
Economic in Indonesia is growing rapidly. One of the supporting factors economic development in Indonesia is the construction field which is growing from year to year. The construction completion process carried out by a construction company has a different period of time depending on the request of the employer. The construction companies measure their gross profit by using the percentage settlement method or the recovered cost method depends on the contract. In general, the contractor company is still wrong in using these methods so that the company does not know clearly the gross profit obtained.The purpose of this study was to determine the recognition of gross profit by applying the recoverable cost method and the percentage of completion method of PT Mitra Menara Mandiri and knowing the factors that influence the selection of methods in the recognition of gross profit using the percentage settlement method and the recoverable cost method at PT Mitra Menara Mandiri.The results of the analysis of the implementation of the cost recovery method and the percentage settlement method of the company's gross profit at PT Mitra Menara Mandiri are still not in accordance with generally accepted accounting principles in terms of determining the recognition of the revenue applied. There is a weakness in the company in recording journals, such as the company does not record business journals when receiving a job and the company does not record if the company conducts billing terms. Therefore, the company should at the time of conducting the billing the company records the journal and records the accounts receivable journal at the time of receiving the job to avoid losing data at the time PT Mitra Menara Mandiri receives cash on the receivables that have been billed.